Arterial tortuosity syndrome: 40 new families and literature review. (October 2018) - Beyens, Aude; Albuisson, Juliette; Boel, Annekatrien; Al-Essa, Mazen; Al-Manea, Waheed; Bonnet, Damien; Bostan, Ozlem; Boute, Odile; Busa, Tiffany; Canham, Nathalie; Cil, Ergun; Coucke, Paul; et al.
Abstract Purpose We delineate the clinical spectrum and describe the histology in arterial tortuosity syndrome (ATS), a rare connective tissue disorder characterized by tortuosity of the large and medium-sized arteries, caused by mutations inSLC2A10 . Methods We retrospectively characterized 40 novel ATS families (50 patients) and reviewed the 52 previously reported patients. We performed histology and electron microscopy (EM) on skin and vascular biopsies and evaluated TGF-β signaling with immunohistochemistry for pSMAD2 and CTGF. Results Stenoses, tortuosity, and aneurysm formation are widespread occurrences. Severe but rare vascular complications include early and aggressive aortic root aneurysms, neonatal intracranial bleeding, ischemic stroke, and gastric perforation. Thus far, no reports unequivocally document vascular dissections or ruptures. Of note, diaphragmatic hernia and infant respiratory distress syndrome (IRDS) are frequently observed. Skin and vascular biopsies show fragmented elastic fibers (EF) and increased collagen deposition. EM of skin EF shows a fragmented elastin core and a peripheral mantle of microfibrils of random directionality. Skin and end-stage diseased vascular tissue do not indicate increased TGF-β signaling. Conclusion Our findings warrant attention for IRDS and diaphragmatic hernia, close monitoring of the aortic root early in life, and extensive vascular imaging afterwards. EM on skin biopsies shows disease-specific abnormalities.